Changing management strategies of a government-hosted festival: The case of Hi Seoul Festival, South Korea. Issue 2 (12th June 2019) - Cho, B. Shine; Lee, Juye; Lee, Wonkang; Min, Hyosang
Abstract : Purpose: The purpose of this paper is to examine the management strategy changes of a government-hosted festival from the government's perspective based on Ansell and Gash's (2008) definitive criteria of collaborative governance. Design/methodology/approach: This is a longitudinal case study of Hi Seoul Festival (HSF) in South Korea from 2003 to 2013. First, a detailed description of HSF management strategy change over time is presented through an analysis of internal government documents. Then, factors influencing management strategy changes are investigated through interviews with governmental and professional stakeholders. Findings: The content analysis of the internal government documents reveals that HSF's management strategy changed between collaborative governance and contracting out multiple times. The follow-up interviews then found that the prehistory experiences in managing festivals, the change of festival goals, and political leverages influenced the management strategy changes. Originality/value: The government is one of the key stakeholders of festivals, which sometimes hosts and manages its own festivals. However, how a government manages its own festival is rarely studied. This study would add new insights into the studies of government-hosted festivals.